Offshoring and the Role of Trade Agreements - Antràs, Pol; Staiger, Robert W (American Economic Review, 2012)
The rise of offshoring of intermediate inputs raises important questions for commercial policy. Do the distinguishing features of offshoring introduce novel reasons for trade policy intervention? Does offshoring create new problems of global policy cooperation whose solutions require international agreements with novel features? In this paper we provide answers to these questions, and thereby initiate the study of trade agreements in the presence of offshoring. We argue that the rise of offshoring will make it increasingly difficult for governments to rely on traditional GATT/WTO concepts and rules—such as market access, reciprocity and non-discrimination—to solve their trade-related problems. (JEL F12, F13, L24)